2021
DOI: 10.1097/ta.0000000000003420
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and neonatal outcomes following maternal aortic balloon occlusion for hemorrhage in pregnancy: A review of the literature

Abstract: BACKGROUND: Hemorrhage is a leading cause of maternal death worldwide, with increased risk in women with abnormal placentation. Aortic balloon occlusion (ABO), including resuscitative endovascular balloon occlusion, has been used for obstetrical hemorrhage for 20 years, and is associated with decreased operative blood loss, fewer transfusions, and lower rates of hysterectomy. However, the effect of aortic occlusion on fetal/neonatal outcomes is not well known. METHODS:A literature review on ABO for obstetrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…3 Several groups have reported superior outcomes with resuscitative endovascular balloon occlusion of the aorta (REBOA) as an adjunct to hemorrhage control during cesarean hysterectomy for PAS. [4][5][6][7][8][9][10][11][12] A meta-analysis of 731 PAS patients who underwent cesarean deliveries in which a REBOA catheter was used to occlude the infrarenal aorta, termed zone 3, found that these women experienced significantly less blood loss, received fewer transfusions, and achieved a higher rate of uterine preservation compared with other hemorrhage control strategies. 9 However, in the 11 studies pooled to generate this metaanalysis, there was no specific standard location of occlusion within zone 3 of the aorta.…”
Section: Questionsmentioning
confidence: 99%
“…3 Several groups have reported superior outcomes with resuscitative endovascular balloon occlusion of the aorta (REBOA) as an adjunct to hemorrhage control during cesarean hysterectomy for PAS. [4][5][6][7][8][9][10][11][12] A meta-analysis of 731 PAS patients who underwent cesarean deliveries in which a REBOA catheter was used to occlude the infrarenal aorta, termed zone 3, found that these women experienced significantly less blood loss, received fewer transfusions, and achieved a higher rate of uterine preservation compared with other hemorrhage control strategies. 9 However, in the 11 studies pooled to generate this metaanalysis, there was no specific standard location of occlusion within zone 3 of the aorta.…”
Section: Questionsmentioning
confidence: 99%
“…The first report on the use of REBOA in the field of obstetrics was in 1995, in a case of PAS 19) . Since then, over 1,000 cases of aortic balloon occlusion have been reported in obstetrics, mainly for cases with PAS to control obstetric hemorrhage during cesarean hysterectomy 20) .…”
Section: Discussionmentioning
confidence: 99%
“…Inflation may begin just after delivery of the infant when the risk of hemorrhage is high, upon vascular pedicle ligation, or may be delayed until hemorrhage is encountered depending on the clinical features of the case. Although there has been as many as 150 published cases of REBOA inflation prior to delivery with reportedly good fetal outcomes in Asia, 10 our practice emphasizes avoiding predelivery aortic occlusion when the fetus is viable.…”
Section: Duration Of Occlusionmentioning
confidence: 96%